Efektifitas Endorphin Massage Terhadap Intensitas Nyeri Persalinan Kala I pada Ibu Bersalin - Tanjung, Wiwi Wardani; Antoni, Adi (Universitas Aufa Royhan, 2019)
Childbirth pain generally occurs in maternity. Pain can cause stress which causes excessive release of hormones such as catecholamines and steroids. This can result in decreased uterine contractions. One way of non-pharmacological management is to reduce labor pain with endorphine massage. Endorphin Massage which is a light touch and massage technique that can normalize heart rate and blood pressure and improve the relaxed condition in the mother's body by triggering a feeling of comfort through the surface of the skin. This Endorphin Massage has never been performed on maternity at the Sahara Maternity clinic in Padangsidimpuan City. This study aims to determine the effectiveness of Endorphin Massage to reduce labor pain. This research was conducted at the Sahara Maternity Clinic in Padangsidimpuan City with the research time starting from March to September 2019. The research design used was a quasi experiment with one group pretest-posttest only design. The sampling technique used was consecutive sampling with a sample of 16 people. The study was conducted in March to June 2019. The measuring instrument used was the Numeric Rating Scale. This study uses paired T test with the results of the first stage of labor pain intensity before the intervention of an average of 6.38 and after the intervention of an average of 5.19. The results showed that Endorphin Massage was effective in reducing the intensity of Kala I labor pain in maternal with a p-value of 0.001. Midwives are expected to use endorphin massage therapy in maternity as a way to reduce pain during labor.